Serum calcium level as a predictor for pregnancy induced hypertension - Itoriya, Sandhya; Singh, Shakun; Dhama, Vandna; Chaudhary, Rachna; Modi, Prapti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy induced hypertension is responsible for causing complications among 7-10% of antenatal females. Intracellular calcium concentrations have been involved in the pathogenesis of pregnancy induced hypertension. To assess estimate serum calcium and assess its the predictive value in development of pregnancy-induced hypertension in 12 to 20 weeks of antenatal women and correlate levels of serum Calcium in pregnancy induced hypertension Methods: A prospective study was conducted in a tertiary care hospital among 400 pregnant females with 12 to 20 weeks of gestation. Blood pressure was measured using sphygmomanometer A detailed family and medical history was taken. Serum calcium levels were measured by the O- cresol phthalein complexone (OCPC) method. Results: Among 400, majority of normotensive patients i.e., 184 had serum calcium levels<9 mg/dl and 91 had between 9-10 mg/dl. 121 patients with pregnancy induced hypertension had serum calcium<9 mg/dl and 4 patients had between 9-10 mg/dl. Among Maternal complications all the 7 patients with eclampsia and 03 with abruption had serum calcium levels<9mg/dl. 70 patients of pre-eclampsia had serum calcium<9 mg/dl and only 04 had between 9-10 mg/dl. Severe pre-eclampsia was seen in 32 patients with serum calcium<9 mg/dl and 01 with 9-10 mg/dl of serum calcium. Fetal complications in form of iugr was seen in 40 pts with serum calcium<9 mg/dl. 4 patients have still birth had s calcium<9 mg/dl. Results were found to be statistically significant(p<0.05). Conclusion: Hypocalcaemia may have a role in causing pregnancy induced hypertension. Thus, intake of calcium supplements helps to reduce its incidence of PIH.